ENHANCING THE ELECTRICAL CONDUCTIVITY OF NYLON 66 VIA THE INCORPORATION OF SILANE-FUNCTIONALIZED GRAPHENE NANOPLATELETS - Shueb, M.I.; Manaf, M.E.A.; Razak, J.A.; Mohamad, N.; Umar, K.N.K.; Doan, V.A. (Journal of Advanced Manufacturing Technology (JAMT), 2023)
Polymer composites have been studied recently as electromagnetic interference (EMI) shielding materials as the need for versatile, low-cost and lightweight materials grows. EMI shielding material is heavily affected by electrical conductivity. One problem associated with utilizing polymers as shielding materials is their inherent non-conductive nature. This study aims to investigate the effects of silane treatment using vinyltrimethoxysilane (VTMS) of graphene nanoplatelets (GNP) on the electrical conductivity of nylon 66 composites reinforced with GNP. The pristine GNP and functionalized GNP were incorporated into the nylon 66 via melt compounding method using twin screw extruder and injection moulding. The functionalization of GNP is found to be significantly improving electrical conductivity of nylon 66 by ten orders of magnitude, from 10-13 to 10-3 S/m. The improvement is attributed to the enhanced dispersion of modified GNP and stronger interfacial interactions between the modified GNP and polymer matrix, which is associated with the covalent linkage of VTMS-GNP with nylon 66. In a nutshell, the VTMS treatment provides an appropriate modification of GNP particles to effectively improve the multifunctional properties of nylon 66/GNP nanocomposites.